Sarana Berpikir Ilmiah (Bahasa, Logika, Matematika Dan Statistika) - Eneng Sumarni; Eti Robiatul Adawiah; Yurna Yurna (LPPM Politeknik Pratama, 2023)
To be able to carry out scientific thinking activities properly, facilities such as language, logic, mathematics, and statistics are needed. The purpose of this research is to explain and analyze the roles of language, logic, mathematics, and statistics as part of scientific thinking tools. Writing this article uses a qualitative method with a descriptive approach and data collection techniques in the form of literature studies. The research results show that language, logic, mathematics, and statistics are important and interrelated and complementary tools of scientific thinking, all of which play an important role in observation, experimentation, analysis, and interpretation of data, as well as in formulating theories and testing hypotheses. The difference between this research and previous research is that it is a means of scientific thinking related to technological advances, methodological developments, and the expansion of knowledge in different fields of science. So thus, understanding and mastering these four means of thinking is important for scientists to be able to understand, develop, and disseminate knowledge effectively in the scientific community.